Recent advances of integrated microfluidic suspension cell culture system. Issue 4 (11th October 2021) - Kerk, Yi Jing; Jameel, Aysha; Xing, Xin‐Hui; Zhang, Chong
Abstract: Microfluidic devices with superior microscale fluid manipulation ability and large integration flexibility offer great advantages of high throughput, parallelisation and multifunctional automation. Such features have been extensively utilised to facilitate cell culture processes such as cell capturing and culturing under controllable and monitored conditions for cell‐based assays. Incorporating functional components and microfabricated configurations offered different levels of fluid control and cell manipulation strategies to meet diverse culture demands. This review will discuss the advances of single‐phase flow and droplet‐based integrated microfluidic suspension cell culture systems and their applications for accelerated bioprocess development, high‐throughput cell selection, drug screening and scientific research to insight cell biology. Challenges and future prospects for this dynamically developing field are also highlighted.